2014
DOI: 10.1002/ab.21540
|View full text |Cite
|
Sign up to set email alerts
|

A self‐report measure of legal and administrative aggression within intimate relationships

Abstract: Although experts agree that intimate partner violence (IPV) is a multidimensional phenomenon comprised of both physical and non-physical acts, there is no measure of legal and administrative (LA) forms of IPV. LA aggression is when one partner manipulates the legal and other administrative systems to the detriment of his/her partner. Our measure was developed using the qualitative literature on male IPV victims' experiences. We tested the reliability and validity of our LA aggression measure on two samples of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 63 publications
3
57
0
Order By: Relevance
“…The victimization scale showed excellent psychometric properties, including good construct, concurrent, and discriminant validity, and good alpha reliability. Construct validity of was supported through significant correlations with other forms of PV victimization and higher rates of LA aggression in the victims sample versus the population-based sample (Hines et al, 2014). This scale contained six dichotomous yes/no questions that assessed whether the participant and/or his partner ever engaged in any of the following behaviors: making false accusations to authorities that the partner physically or sexually abused the other, making false accusations to authorities that the partner physically or sexually abused the children, leaving and taking the children away, leaving and taking all the money and possessions, ruining the partner’s reputation at work, and ruining the partner’s reputation in the community.…”
Section: Methodsmentioning
confidence: 96%
“…The victimization scale showed excellent psychometric properties, including good construct, concurrent, and discriminant validity, and good alpha reliability. Construct validity of was supported through significant correlations with other forms of PV victimization and higher rates of LA aggression in the victims sample versus the population-based sample (Hines et al, 2014). This scale contained six dichotomous yes/no questions that assessed whether the participant and/or his partner ever engaged in any of the following behaviors: making false accusations to authorities that the partner physically or sexually abused the other, making false accusations to authorities that the partner physically or sexually abused the children, leaving and taking the children away, leaving and taking all the money and possessions, ruining the partner’s reputation at work, and ruining the partner’s reputation in the community.…”
Section: Methodsmentioning
confidence: 96%
“…We also added six items to measure men's perpetration and victimization from legal/administrative aggression, which included making false accusations to authorities that the partner physically or sexually abused the other, making false accusations to authorities that the partner physically or sexually abused the children, leaving and taking the children away, leaving and taking all the money and possessions, ruining the partner's reputation at work, and ruining the partner's reputation in the community. Previous analyses of this subscale with the current sample showed that it has excellent psychometric properties, including good construct validity and good alpha reliability (Hines, Douglas, & Berger, 2014).…”
Section: Revised Conflict Tactics Scales (Cts2)mentioning
confidence: 98%
“…One notable absence is the measurement of legal and administrative (LA) aggression, which Tilbrook, Allan, and Dear () define as the manipulation of legal and administrative resources in an attempt to control or inflict emotional and financial harm on one's partner. In a previous paper, we documented the psychometric properties of a LA aggression scale among two samples: male victims of physical IPV who sought help and a population‐based sample of men (Hines et al, ). The purpose of this paper is to investigate the potential mental health consequences of LA aggression on men who sought help for physical IPV and their children.…”
Section: Introductionmentioning
confidence: 99%
“…LA aggression occurs when one partner uses the legal and administrative system (e.g., courts, law enforcement, child protection services) either during or after the termination of a relationship in an abusive manner, and this can often involve false allegations against the victims. In our conceptualization and measurement of LA aggression, we measured both threats of aggression and actual aggression (Hines et al, ).…”
Section: Introductionmentioning
confidence: 99%